Respuesta :
Answer:
x + y + z.
Step-by-step explanation:
x² + y² + 2xy - z²
= (x + y)^2 - z^2
This is the difference between 2 squares so the factors are:
(x + y + z) and (a + y - z).
Answer: The factors are (x+y+z) and (x+y-z)
In other words, it factors to (x+y+z)*(x+y-z)
=====================================================
Work Shown:
[tex]x^2 + y^2 + 2xy - z^2\\\\(x^2 + 2xy + y^2) - z^2\\\\(x+y)^2 - z^2\\\\(x+y+z)(x+y-z)\\\\[/tex]
Notes:
- In the third step, I used the rule (A+B)^2 = A^2+2AB+B^2. For this, A = x and B = y.
- In the last step, I used the difference of squares factoring rule A^2-B^2 = (A+B)(A-B). In this case, A = x+y and B = z.